Mixing of EFB Fibre - Liquid in Stirred Tank Using Intermig Impellers - Muhammad Hairynizam, Muhd Taib; Jolius, Gimbun (2012)
Mixing process involving palm oil empty fruit bunch (EFB) and liquid such as in production of the carboxyl methyl cellulose has never been studied. Better understanding of their mixing performance is of great interest in process design and scale-up. This paper presents mixing of palm oil empty fruit bunch (EFB) fibre-liquid in a stirred tank agitated by two Intermig impellers. The tank dimension was H=1.4T with the impeller diameter of 25.5 cm fixed at T/3 and 2T/3, respectively. Measurement of the power draw was carried out using an IKA Eurostar torque meter for a wide range of impeller speed. The result shows relative power draw increases as concentration of EFB fibre increases. The relative power draws increases as much as 5 times higher when concentration of EFB fibre increases from 1 wt.% w/w to 4 wt.%, which suggests higher operational power requirement. The result also suggests that a constant power number (desired mixing characteristic) can be achieved when the tank operates at Reynolds's number above 60000. The Intermig impellers are capable of handling up to 4 wt.% of EFB fibre, which is a significant improvement compared to conventional solid mixing impeller such as the pitched blade impeller which is limited to 2 wt.%. Results from this work might be useful for an efficient design of EFB-liquid mixer or reactor.